2010
DOI: 10.1080/10410236.2010.521912
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Michigan Organ Donor Registry: Evaluating the Impact of a Multifaceted Intervention Utilizing Media Priming and Communication Design

Abstract: There are currently more than 100,000 individuals waiting for an organ transplant. Organ donor registries represent the easiest and most concrete way for people to declare their intent to donate, but organ donor registries are vastly underutilized. This study reports a campaign intervention designed to increase the rate of joining the Michigan Organ Donor Registry. Grounding intervention development in the theoretical principles of media priming and communication design, the intervention took place in two wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 16 publications
1
49
0
Order By: Relevance
“…Campaigns featuring a combination of media and interpersonal components have been found to be more effective in increasing knowledge, attitudes, norms, intentions, and behaviors toward organ donation than media campaigns alone (Feeley & Moon, 2009;Harrison et al, 2010). More generally, research has suggested that 808…”
Section: Interpersonal Communication and Health Campaignsmentioning
confidence: 96%
“…Campaigns featuring a combination of media and interpersonal components have been found to be more effective in increasing knowledge, attitudes, norms, intentions, and behaviors toward organ donation than media campaigns alone (Feeley & Moon, 2009;Harrison et al, 2010). More generally, research has suggested that 808…”
Section: Interpersonal Communication and Health Campaignsmentioning
confidence: 96%
“…The health care provider is capitalising upon the use of e-technology in forging a closer physicianpatient relationship (Sundar et al 2011). Communications beyond the face-to-face consultation allow patients to receive and share a wider range of clinical information such as chronic disease self-management (Prestin and Chou 2014) and interventional evaluation (Harrison et al 2010). Meanwhile, it is reported the use of peer-to-peer (P2P) communication is useful in developing competence in understanding technical information and in accessing relevant health provider.…”
Section: Global Diversity In Health Communication and Everyday-ing Hementioning
confidence: 99%
“…The placement of materials was determined by principles of communication design (e.g. Aakhus, 2007;Harrison et al 2010;Jackson, 1998) to encourage positive interactions about organ donation. Materials for each set of interventions modified for the target audiences of each county.…”
Section: The Michigan Tell Us Now Dmv Campaignmentioning
confidence: 99%
“…facebook) are being investigated for their ability to generate new potential donors, the results of those studies are not yet know. However, a series of recent studies (Harrison et al, 2008;Harrison et al, 2010;Harrison et al, 2011;King et al, under review) have demonstrated the ability to overcome this limited reach and provide dramatic increases in the rates of joining organ donor registries (ranging from 200% to over 500% with net increases in the tens of…”
Section: Introductionmentioning
confidence: 99%